The dynamics of psychological contract between employee and organization. The analysis of selected factors = Dynamiczny charakter kontraktu psychologicznego pomiędzy pracownikiem a organizacją. Analiza wybranych warunków - Mazur, Karolina (Zielona Góra: Faculty of Economics and Management Press)
The main purpose of this paper was the examination if the psychological contract between an employee and organization has a dynamic character and how the age and experience progress influences the contract in terms of contract content, values offered by employees and the contract breach. The paper consists of own research findings of the author. The group of 140 employees from high-tech industry were examined in period of 2010-2011. There was used a [X]2 test in assessment of assumed relations. The research findings proved that the conditions of psychological contract changed with age of employee and his or her stage in the workplace. It refers to both parts of the contract. Values expected and values offered by employee evolves. The age and stage in the workplace change are also connected with change of employee perception of the type of contract breach. The research findings demonstrated that psychological contract is dynamic phenomenon.
Keywords: pracownik a organizacja; pracownicy sektora wysokich technologii; employee and organization; employees from hight-tech industry